Phase composition, structure and stress state of magnetron sputtered W-Ti condensates - Sobol`, O.V. (Functional Materials, 2006)
The effects of elemental composition and deposition temperature on W—Ti ion-plasma condensate structure, substructure characteristics and stress state have been studied. The crystalline state of all phases formed during deposition has been found to be based on the α-W bcc crystalline lattice. In the initial stages of solid solution formation under relatively low content of substituting titanium atoms in the lattice (7 to 11 at.%), oriented crystallite growth takes place with (100) planes parallel to the condensate surface. At higher titanium atomic content in the lattice, strongly strained crystallites of (W₁₋ₓ, Tiₓ) solid solution are formed with light preferential orientation of (110) plane parallel to the growth surface. In this case, the deposition temperature elevation from 300°C to 800°C results in concentration stratification of the formed solid solution followed by formation of two solid solutions with different stable elemental composition. The diffusion coefficient in nano-crystalline W—Ti condensates has been estimated and models describing the formed condensate structure state are proposed.